Copper-Catalyzed C–N Cross-Coupling of Substituted 2-Halobenzoates with Secondary Acyclic Amides - Wang, Man-Gang; Yu, Hua; Wu, Jun; Shang, Zhi-Cai (Synthesis, 2013)
The copper-catalyzed C–N cross-coupling of poorly nucleophilic acyclic secondary amides with sterically hindered substituted 2-halobenzoates has been demonstrated with 1,4-dimethyl-3,4-dihydro-1H-benzo[e][1,4]diazepin-5(2H)-one (DMBDO) as ligands for the first time. The protocol is effective for the synthesis of hindered tertiary amides. We also found that the alkoxycarbonyl (CO2R) group has a strong ortho-substituent effect on a Goldberg-type C–N coupling reaction.
Keywords: copper; N-arylation; cross-coupling; amides; halobenzoates